Hubungan Oligohidramnion Terisolasi saat Aterm dengan Modus Persalinan - Dalya Thamer Ahmed; Shaymaa Abed Hasan (Neolectura, 2022)
To assess the relationship of between isolated oligohydramnios at the last few weeks of pregnancy with mode of delivery and evaluate its role in failure of induction of labor and its role in increase rate of caesarian section. This is a case-control study was carried out including 70 pregnant women,35 of them with normal amount of liquor (control group), and the other 35 pregnant women with isolated oligohydramnios diagnosed according to ultrasound criteria (amniotic fluid index of 5 cm, single deepest pocket of 2 cm) (study group) , all pregnant women at (37-40 weeks) of gestation, attended the ANC unit in Nu'man Teaching Hospital and the outpatient private clinics in Hay Aljameaa/ Al-Harthya in Baghdad from December 2020 till April 2021. Study group includes 35 pregnant women with isolated oligohydramnios and the control group includes 35 pregnant women with normal AFI after matching of other inclusion criteria (maternal age, parity and gestational age) for both groups, there is a significant difference between the study and control group in mode of delivery as the highest percent of women with IO delivered by cesarean section (68.57%) while the highest percent of women with normal AFI delivered vaginally (74.29%). There is a statistical difference in the rate of cesarean section due to abnormal doppler study before induction of labor (p value= 0.0500), there is significant difference in mean birth weigh between both study groups (P-value= 0.0380), with the statistically significant differences in Apgar score at 1 minute and 5 minutes ?7/10 (P-value = 0.0047, 0.0253) respectively. With high level of significancy about neonatal intensive care unit admission (NICU)Admission > 24hrs (P-value= 0.0110). Pregnancies with isolated oligohydramnios are associated with increased rate of development of fetal distress, meconium-stained liquor, rate of caesarean delivery, NICU admission and low birth weight. Rate of cesarean for fetal distress is increased because of increased rate of induction of labor in the women with oligohydramnios. The study does not suggest any root for delivery of pregnancies with IO, It is better to give the patient chance of spontaneous labor (if there is no fetal distress) with close monitoring for the fetal heart rate during labor. Cesarean section is indicated for IO with fetal distress at any stage of labor to decrease perinatal morbidity and mortality. Further studies may be required to evaluate the long-term consequences of isolated oligohydramnios.